2014
DOI: 10.1097/aci.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach allergy and allergen-specific immunotherapy in asthma

Abstract: Purpose of review To provide a summary and discussion of cockroach allergy and clinical trials of cockroach allergen immunotherapy. Recent findings Cockroach allergen exposure among sensitized children is increasingly recognized as a key factor contributing to asthma morbidity. Recent trials suggest that cockroach immunotherapy has promise as a treatment strategy with studies demonstrating immunomodulatory and clinical effects. However, a few obstacles need to be overcome to realize the full potential of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…A limited number of clinical trials using cockroach allergen extracts showed improvement in both immunological and clinical parameters [59,117] (Table 2). Kang et al in 1988 reported in a small number of patients (n = 11) that immunotherapy with cockroach extract resulted in improvement of immunological and clinical parameters after five years of treatment [118].…”
Section: Cockroach Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of clinical trials using cockroach allergen extracts showed improvement in both immunological and clinical parameters [59,117] (Table 2). Kang et al in 1988 reported in a small number of patients (n = 11) that immunotherapy with cockroach extract resulted in improvement of immunological and clinical parameters after five years of treatment [118].…”
Section: Cockroach Immunotherapymentioning
confidence: 99%
“…The pediatric SLIT study (n = 99) revealed significant differences in IgE, IgG, and IgG4 responses between both active groups and the placebo group but no consistent differences between the high- and low-dose groups. The SCIT adult study (n = 10) found that the treatment resulted in significant changes from baseline in cockroach IgE, IgG4, and blocking antibody levels [117]. No further clinical trials conducted with cockroach extracts have been reported.…”
Section: Cockroach Immunotherapymentioning
confidence: 99%
“…Thus, it is essential to have the standardized cockroach extracts with reliable potency and contents for the diagnosis of cockroach allergy. Similarly, cockroach immunotherapy for cockroach allergy holds promise as a treatment strategy with immune-modulatory and clinical effects in a limited number of trials (22-25), but the lack of standardized cockroach extracts limit their potential to provide optimal clinical efficacy to patients. Thus, further works are needed to identify major allergenic components in cockroach and clone immunodominant cockroach allergens in order to provide therapeutic cockroach allergen products with enhanced clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the utility of immunotherapy and its effect on allergic asthma has been disputed [47][48][49]. The clinical effectiveness of immunotherapy with cockroach and mouse extracts for asthma or allergic rhinitis has been investigated in only a limited number of studies [50][51][52]. This has prompted the National Institute of Allergy and Infectious Diseases to develop cockroach and mouse extract immunotherapy protocols, with the intent to develop new therapies for cockroach and mouse allergy.…”
Section: Modifying Host Response To Pest Allergen Exposures: Focusingmentioning
confidence: 99%